Integrating mine closure planning with environmental impact assessment: challenges and opportunities drawn from African and Australian practice - Morrison-Saunders, A.; McHenry, M. P.; Sequeira, A.; Gorey, P.; Mtegha, H.; Doepel, D. (Impact Assessment and Project Appraisal, 2016)
Best practice mine closure planning and environmental impact assessment (EIA) principles share many common features. This research examined how mine closure planning relates to, and can be integrated with EIA by comparing practice in eight African and Australian jurisdictions. Emphasis was placed on key challenges and opportunities associated with: institutional arrangements for mine closure planning; financial mechanisms for mine site closure and rehabilitation including abandoned/legacy mine sites; transparency of mine closure planning and financing provisions; and regulation of artisanal and small-scale mining activity. Data were gathered through document analysis, interviews and interactions with practitioners from Western Australia, Ghana, Kenya, Nigeria, Mozambique, South Africa, Tanzania and Zambia. Issues associated with mine closure planning and rehabilitation under existing arrangements and opportunities for improvement through existing EIA processes already in place in each jurisdiction are explored. All eight jurisdictions have appropriate regulatory provisions in place already, but implementation capacity remains a challenge. Opportunities for effective practice lie in using mine closure planning and EIA measures in an integrated fashion, avoiding duplication and enabling synergies in management to be realised.